An attempt to support by the Japanese society of travel and health for increasing travel clinics()() - Watanabe, Hiroshi (J Infect Chemother, 2018)
In recent years, both the number of Japanese travelers to foreign countries and foreign travelers who visit Japan have increased remarkably, and the risk of travelers suffering various infectious diseases is also increasing. In many western countries travel clinics commonly perform medical consultations, vaccinations, and issue prescriptions. However, travel clinics are not yet popular in Japan. In 2011, Japanese society of travel and health (JSTH) began a support project for travel clinic with a goal of increasing their number throughout the country. The project included the release of a manual for education, training, equipment, details of medical treatment, sources of information for travel clinic opening on the JSTH website (http://jstah.umin.jp/20TravelClinicSupport/manual_20120726.pdf), and mediation of short-term visitation to experienced travel clinics registered in the JSTH to facilitate learning above information and aftercare services. JSTH accepted requests for visitation to travel clinics from 39 medical institutions between 2011 and 2018. By 2018, 26 (66.7%) of the 39 medical institutions had opened travel clinics within two years and the 25 travel clinics had registered in the JSTH and one was a campus-limited clinic, while most of the remaining institutions are still in preparation stages. The number of travel clinics registered in the JSTH has increased from 45 in 2011 to 108 in 2018. Twenty-five travel clinics registered in the JSTH between 2011 and 2018 were eventually receiving support from JSTH. Our data indicates travel clinics in Japan have gradually increased and establishment areas are expanding after the beginning of support project for travel clinics by JSTH.